Method for preparing lithium-rich silicon monoxide negative electrode material by utilizing photovoltaic crystalline silicon waste material

By preparing lithium-rich silicon oxide sub-material materials with photovoltaic crystalline silicon waste and building a three-dimensional conductive network, the problem of degradation of volume expansion and cycling performance of silicon-based materials in lithium-ion batteries is solved, and a negative electrode material preparation with high energy density and stability is achieved , reducing resource waste and environmental pollution.

CN119252879AInactive Publication Date: 2025-01-03CHINA ENERGY CONSERVATION ENG TECH RES INST CO LTD

Patent Information

Application Number
CN202411251028.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Scrapped solar panels in the photovoltaic industry contain a large amount of high-purity silicon materials, which are difficult to effectively recycle and utilize in the existing technology, resulting in waste of resources and environmental pollution. At the same time, the volume expansion and cycling performance of silicon-based materials during lithium-ion embedding are reduced, making it difficult to meet the battery. Energy density requirements.

Method used

By crushing photovoltaic crystalline silicon waste into nanoscale, silicon oxide materials are prepared, and lithium-rich silicon oxide particles are calcined with lithium-rich compounds. A three-dimensional conductive network is constructed using carbon coating technology to form high energy density and stability Carbon-coated lithium-rich silicon oxide negative electrode material.

Benefits of technology

Effectively utilize photovoltaic silicon crystal waste, reduce resource waste and environmental pollution, improve the first-time Coulomb efficiency and cycling performance of the battery, suppress the volume expansion problem, and enhance the conductivity and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252879A_ABST
    Figure CN119252879A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic crystalline silicon waste treatment, and discloses a method for preparing a lithium-rich silicon monoxide negative electrode material from photovoltaic crystalline silicon waste, and the method comprises the following steps: step 1, crushing and granulating the photovoltaic crystalline silicon waste; 2, preparing silicon monoxide particles; step 3, preparing lithium-rich silicon monoxide particles; step 4, preparing carbon-coated lithium-rich silicon monoxide particles; and 5, constructing a conductive network of the carbon-coated lithium-rich silicon monoxide particles to obtain the carbon-coated lithium-rich silicon monoxide negative electrode material with the three-dimensional conductive network. According to the scheme, high-value utilization is carried out on the photovoltaic silicon crystal waste, and the problem of subsequent treatment of solid waste is solved; the source pressure of the silicon-based negative electrode material is effectively relieved, and the preparation cost pressure of the silicon-based negative electrode material is reduced; the problems of low initial coulombic efficiency, obvious volume expansion, poor conductivity and the like of the silicon-based negative electrode material are solved by carrying out pre-lithiation, carbon coating, net coating, doping and the like on the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic crystalline silicon waste treatment, and in particular to a method for preparing lithium-rich silicon oxide negative electrode material by utilizing photovoltaic crystalline silicon waste. Background Art

[0002] Since 2000, my country's photovoltaic industry has risen rapidly and has become the world's largest manufacturer of solar photovoltaic products. Currently, the service life of solar panels is mostly 20 to 30 years. It is expected that in the next few years, a large number of solar panels will gradually enter the scrap stage. However, scrapped solar panels contain a large amount of high-purity silicon materials. Therefore, a method is urgently needed to recycle these silicon-based materials to reduce resource waste and reduce negative impacts on the environment.

[0003] The applicant analyzed that a feasible way is to recycle these silicon materials to make negative electrode materials for lithium batteries, because graphite is currently used as negative electrode material in the field of power batteries and energy storage batteries, and its theoretical specific capacity is only 372mAh / g, which is difficult to meet the growing energy density demand of the battery industry. Theoretical calculations show that at room temperature, the theoretical specific capacity of the silicon-based negative electrode is 3579mAh / g, which is much higher than the graphite negative electrode, showing a good energy density; and the silicon-based material itself has low toxicity, less harm to the human body and the environment, and its easy recycling and reuse renewability is in line with the concept of green development. Of course, although silicon-based materials have excellent prospects for use as battery negative electrodes, there are still some technical problems in the use process: 1. Silicon will expand by up to 300% in volume during the lithium ion embedding process, destroying the structure, weakening the service life of the battery, and reducing the battery's first coulomb efficiency; 2. Affected by the expansion and collapse of the electrode volume, the block material of the silicon-based negative electrode will gradually pulverize and fall off during multiple charge and discharge processes, resulting in capacity decay and decreased cycle performance; 3. The conductivity of silicon materials is relatively low. Summary of the invention

[0004] The present invention aims to provide a method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste, so as to solve the problem of large amounts of high-purity silicon material waste in scrapped solar panels.

[0005] To achieve the above object, the present invention adopts the following technical solution: a method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste, comprising the following steps:

[0006] Step 1: Crushing and granulating photovoltaic silicon crystal waste: crushing bulk photovoltaic silicon crystal waste to reduce its size to nanometer level;

[0007] Step 2: Preparation of silicon dioxide particles: Dissolve the crushed photovoltaic silicon crystal waste in an organic solvent of NaOH, then filter, wash and dry the product, and send the dried silicon crystal waste into a sublimation furnace for sintering at a sintering temperature of 300 to 1100° C. to obtain bulk silicon dioxide material;

[0008] Step 3: Preparation of lithium-rich silicon oxide particles: crushing and pulverizing the block silicon oxide material into nano-sized particles, and roasting the silicon oxide particles and the lithium-rich compound at a roasting temperature of 200 to 1200° C. to obtain lithium-rich silicon oxide particles;

[0009] Step 4: Preparation of carbon-coated lithium-rich silicon oxide particles: reacting the lithium-rich silicon oxide particles with a carbon source compound at a temperature of 300 to 1000° C. to obtain lithium-rich silicon oxide particles with a sandwich structure, wherein the inner layer is silicon oxide, the middle layer is lithium-rich silicon oxide, and the outer layer is an amorphous carbon coating layer;

[0010] Step 5: Construct a conductive network of carbon-coated lithium-rich silicon oxide particles: Mix and ball-mill the carbon-coated lithium-rich silicon oxide particles, single-walled nanotubes, and phosphorus-containing sintering aids. The single-walled carbon nanotubes are wrapped around the surface of the lithium-rich silicon oxide particles to form a three-dimensional network structure, thereby obtaining a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network.

[0011] Preferably, in step 1, a sand grinding method is used to reduce the size of the photovoltaic silicon crystal waste.

[0012] Preferably, the dispersion solvent in the sand milling process of step 1 is a water-based solvent or an organic solvent, the sand milling medium is zirconium oxide sand with a size of 10um to 2nm, and the sand milling time is 0.5 to 3 hours. During the sand milling process, the dispersion stability of the particles can be further improved by the combined action of the dispersion solvent and the sand milling medium.

[0013] Preferably, in step 2, the sintering oxidation time is 1 to 10 hours, the heating rate of the sintering temperature is 2 to 15° C. / min, and the temperature is naturally cooled after sintering; and the concentration of NaOH is 0.1 to 2 mol / L.

[0014] Preferably, in step 3, the blocky silicon oxide is crushed into silicon oxide powder by sand milling, the dispersing solvent in the sand milling process is 95% to 99% ethanol, the sand milling time is 0.5 to 3 hours, the sand milling medium is zirconium oxide sand with a size of 10um to 2nm, and the size of the silicon oxide after sand milling is 10 to 900nm. In the sand milling process, the dispersion stability of the particles can be further improved by the action of the dispersing solvent and the sand milling medium together.

[0015] Preferably, the slurry after sand grinding in step 3 is spray dried to obtain silicon dioxide particles, the spray drying feed temperature is 40-100°C, the outlet air temperature is 80-200°C, the air flow rate is 0.5-3m / s, and the droplet size is 10-200um.

[0016] Preferably, the silicon dioxide particles in step 3 are subjected to a high-temperature solid-phase alloy reaction with a lithium-rich compound under the protection of an inert gas to obtain lithium-rich silicon dioxide particles; the lithium-rich compound comprises one or more of lithium hydroxide, lithium carbonate, lithium silicate, lithium fluoride, lithium hydroxide, and lithium sulfate; the silicon dioxide powder has a particle size distribution of 1 to 30 um, a mass ratio of silicon dioxide to lithium-rich compound of 1 to 100:1, a high-temperature solid-phase reaction time of 1 to 36 h, a controlled heating rate of 2 to 20°C / min, and the reaction is cooled naturally; the inert gas is argon or nitrogen, and the gas flow rate is 0.2 to 10 L / min.

[0017] Preferably, the amorphous carbon layer of the lithium-rich silicon oxide particles in step 4 is formed by carbon coating produced by decomposition of carbon-containing organic matter at 300-1000°C, the lithium-rich silicon oxide particles react with the carbon-containing organic matter under inert conditions, the particle size distribution of the lithium-rich silicon oxide powder is 1-50um, the mass ratio of carbon-containing organic matter to lithium-rich silicon oxide powder is 100-500:1, the high-temperature reaction time is 1-20h, the heating rate is controlled to be 1-25°C / min, the furnace speed is 1-10r / min, the inert gas is argon or nitrogen mixed with hydrogen, the inert gas supply flow rate is controlled to be 1-10L / min, the inert gas supply flow rate ratio of inert gas to hydrogen is 1-15:1, and the reaction is naturally cooled after the reaction; the carbon-containing organic matter includes: one or more of glucose, sucrose, polyols, polyvinyl alcohol, polystyrene, starch, and polyacrylonitrile. During the reaction, inert gas argon needs to be introduced as a protective gas, and a small amount of hydrogen is introduced at the same time to adjust the decomposition process of the carbon source, control the deposition rate and morphology of carbon, promote the cracking of the carbon source, and prevent excessive deposition.

[0018] Preferably, in step 5, under the protection of inert gas, a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network is prepared by high-energy ball milling; the lithium-containing sintering aid includes: one or more of lithium oxyborate, lithium carbonate, lithium fluoride, lithium oxide, lithium triphosphate, lithium chloride, and lithium silicate; the mass ratio of the carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes and the lithium-containing sintering aid is 5-8:1-4:1, the ball milling medium is zirconia balls, alumina balls or silicon nitride balls, the ball milling time is 1-8 hours, and the ball milling speed is 150-600r / min.

[0019] The present invention also provides a method for manufacturing an electrode sheet using the carbon-coated lithium-rich silicon oxide negative electrode material having a three-dimensional conductive network, comprising the following steps:

[0020] a. Prepare a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network, acetylene black, and sodium carboxymethyl cellulose in a mass ratio of 6:2:2, then add deionized water and anhydrous ethanol, the volume ratio of deionized water to anhydrous ethanol is 7.5:2.5, stir for 6 to 10 hours, and prepare a uniform slurry;

[0021] b. The slurry is evenly coated on the Cu foil, the coating speed ratio is controlled at 20% to 30%, the temperature during the coating process is controlled at 50 to 90°C, and after the coating is completed, the Cu foil is placed in a vacuum drying oven for drying at a constant temperature of 90°C for 10 hours to obtain a pole piece;

[0022] c. Compact the electrode sheet with a roller press, and then punch it into an electrode sheet with a preset diameter with a slicer. Screen the electrode sheet to obtain a complete and crease-free electrode sheet. After assembling and buckling, use a sealing machine to seal it.

[0023] Sealing with a sealing machine combined with a rolling process can increase the density of the electrode material and increase the capacity. Good contact is beneficial to improving ion transfer efficiency.

[0024] Advantages of this solution:

[0025] 1. The raw materials of the present invention are derived from photovoltaic silicon crystal waste, which is relatively low in price and high in purity. Considering the rapid development of the photovoltaic industry in recent years and the scrap cycle of solar panels of about 20 years, photovoltaic silicon crystal waste is an abundant source of raw materials;

[0026] 2. The present invention uses dry process in the process of preparing negative electrode materials, which reduces the influence of solvent on material properties (such as capacity and cycle stability), and controls the pollution to the environment caused by byproducts that are inevitably generated when the solvent is used, thereby reducing the cost of using chemical solvents;

[0027] 3. Through layer-by-layer coating, a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network was prepared. Compared with carbon coating on pure silicon, the catalytic reaction of pyrolytic carbon will lead to the problem of difficulty in coating amorphous carbon on pure silicon. In this scheme, silicon dioxide has a good balance between capacity and cycle performance. Pre-lithiated silicon oxide can improve the first coulomb efficiency of the material, and the carbon coating layer will improve the conductivity of the material. The outermost phosphorus-doped single-walled carbon nanotubes effectively suppress the volume expansion problem of silicon oxide materials during lithium insertion through their own excellent mechanical properties, reduce the breakage and reconstruction problems of SEI film, and improve the stability of the material. At the same time, phosphorus doping can provide more electron donors, change the band gap width of the material, introduce band gap defect energy levels, and improve the conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the process of preparing a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network using photovoltaic crystalline silicon waste in an embodiment of the present invention.

[0029] Figure 2 Schematic diagram of the structure of a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network according to an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following is further described in detail through specific implementation methods:

[0031] The reference numerals in the drawings of the specification include: silicon oxide layer 1, lithium-rich silicon oxide layer 2, amorphous coating carbon layer 3, phosphorus-doped conductive three-dimensional network carbon nanotube 4.

[0032] The present application provides a method for preparing lithium-rich silicon oxide negative electrode materials using photovoltaic crystalline silicon waste, which effectively promotes the green and recyclable development of the economy by efficiently utilizing high-purity silicon in discarded solar panels to avoid waste accumulation and environmental pollution. The present application constructs a sandwich structure, such as the attached Figure 2 As shown, the innermost layer is a silicon oxide layer 1, the second innermost layer is a lithium-rich silicon oxide layer 2 after pre-lithiation, the second outermost layer is an amorphous coating carbon layer 3, and the outermost layer is a phosphorus-doped conductive three-dimensional network carbon nanotube 4 material, which effectively suppresses the volume expansion, poor conductivity, low first-cycle coulomb efficiency and other problems of silicon-based negative electrode materials. The specific preparation method is shown in the attached Figure 1 shown.

[0033] Embodiment 1:

[0034] A method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste comprises the following steps:

[0035] (1) Crushing and granulating photovoltaic silicon crystal waste: The photovoltaic silicon crystal waste is sent to a sand mill for sand milling. To avoid the introduction of metal impurities, the sand milling medium size is selected from 10um to 2nm zirconium oxide sand, preferably 2nm zirconium oxide sand, the sand milling time is 0.5 to 3h, preferably 3h, the dispersion solvent is a water-based solvent or an organic solvent, and the dispersion solvent is specifically 95% industrial ethanol solvent. The sand milling detects the silicon powder particle size D 50 In the range of 200 to 800 nm, preferably 250 nm.

[0036] (2) Preparation of silicon dioxide material: Add 1 mol / L NaOH solution to the sand-ground nanoscale photovoltaic silicon crystal slurry until it is excessive, stir it thoroughly for 2 hours to react and remove the metal element aluminum, then filter and wash the product, and put the silicon powder into a vacuum drying oven at 80°C to remove the surface moisture of the silicon powder. The drying time is about 24 hours. The dried silicon powder is sent to a sublimation furnace and sintered for 6 hours at a heating rate of 15°C / min and a sintering temperature of 800°C. The silicon dioxide block material is obtained by natural cooling.

[0037] (3) Preparation of lithium-rich silicon dioxide particles:

[0038] a. Pulverize the blocky silicon oxide with a sand mill. The dispersing solvent in the sand milling process is 95% to 99% ethanol, preferably 99% ethanol. 99% ethanol has higher volatility and faster subsequent drying speed. The sand milling time is 0.5 to 3 hours, preferably 3 hours. The sand milling medium is zirconium oxide sand with a size distribution of 10um to 2nm, preferably 2nm zirconium oxide sand, which improves the solubility and drying speed of the subsequent process. The size of the silicon oxide after sand milling is D 50 The sand-milled silicon dioxide is dissolved in 99% ethanol and dried by spray drying. The sand-milled slurry is spray-dried to obtain silicon dioxide particles. The feed temperature of the spray drying is 40 to 100°C, preferably 60°C, the outlet air temperature is 80 to 200°C, the air flow rate is 0.5 to 3 m / s, and the droplet size is controlled at 10 to 200 um.

[0039] b. The obtained dry silicon oxide particles and lithium-rich compounds are subjected to high-temperature solid-phase alloy reaction under the protection of an inert gas environment, and lithium-rich silicon oxide particles are obtained through high-temperature solid-phase alloy reaction. The particle size of silicon oxide powder is 1 to 30 um, the mass ratio of silicon oxide to lithium-rich compound is 1 to 100:1, the high-temperature solid-phase reaction time is 1 to 36 hours, the heating rate is controlled to be 2 to 20°C / min, the temperature is naturally cooled, the sintering temperature is 200 to 1200°C, the inert gas introduced is argon or nitrogen, and the gas flow rate is 0.2 to 10 L / min.

[0040] In this embodiment, the pre-lithiation reagent is prepared by compounding lithium carbonate, lithium silicate, and lithium oxide in a mass ratio of 4:4:2. The mass ratio of the compounded pre-lithium compound to the silicon dioxide particles is 1:20. The high-temperature solid phase reaction time is controlled at 12 h, the heating rate is 5°C / min, the sintering temperature is 400°C, argon is introduced as a protective gas, the gas flow rate is controlled at 4L / min, and the reaction is naturally cooled after completion.

[0041] (4) Preparation of lithium-rich silicon oxide particles with a carbon-coated structure: Carbon is coated on the surface of lithium-rich silicon oxide by high-temperature chemical vapor deposition, wherein the particle size distribution of lithium-rich silicon oxide powder is 1-50 um, the mass ratio of carbon-containing organic matter to lithium-rich silicon oxide powder is 100-500:1, the high-temperature reaction time is 1-20 hours, the heating rate is controlled at 1-25°C / min, and the temperature is naturally cooled. The sintering temperature is 300-1000°C, the furnace speed is 1-10 r / min, and the inert gas introduced is argon and nitrogen, mixed with a small amount of hydrogen, the inert gas supply flow rate is controlled at 1-10 L / min, and the inert gas: hydrogen: supply flow rate ratio is 1-15:1.

[0042] The carbon source materials selected in this embodiment are organic substances that are easily decomposed by heat - glucose, starch and polyvinyl alcohol, which are obtained by compounding in a mass ratio of 2:2:6. The mass ratio of the compounded carbon source material to the lithium-rich silicon oxide particles is 100:1. The reaction time is controlled at 2h, the heating rate is 10℃ / min, the sintering temperature is 850℃, and the furnace body needs to maintain a reasonable rotation speed to ensure uniform coating. The rotation speed is controlled at 2r / min. During the reaction, inert gas argon needs to be introduced as a protective gas, and a small amount of hydrogen is introduced at the same time to adjust the decomposition process of the carbon source, control the deposition rate and morphology of carbon, promote the cracking of the carbon source, and prevent excessive deposition. The mass ratio of the mixed argon and hydrogen is 9:1, and the gas flow rate of argon is controlled at 6L / min.

[0043] (5) Constructing a three-dimensional conductive network of carbon-coated lithium-rich silicon oxide particles: The carbon-coated lithium-rich silicon oxide particles, single-walled nanotubes, and lithium-containing sintering aids are mixed and ball-milled, and the single-walled carbon nanotubes are wrapped on the surface of the lithium-rich silicon oxide particles to form a three-dimensional network structure, thereby obtaining a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network. In this step, single-walled carbon nanotubes are selected as the main framework for constructing the conductive network, and lithium-containing phosphates are added as sintering aids to improve the conductivity of the material.

[0044] The mass ratio of carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes and lithium-containing sintering aids is 5-8:1-4:1, and the ball milling medium can be selected from zirconium oxide balls, aluminum oxide balls and silicon nitride balls, etc. The ball milling time is 1-8 hours, and the ball milling speed is 150-600r / min. High-energy ball milling needs to be carried out in an inert gas protection atmosphere, and the selected inert gas is nitrogen or argon. After the ball milling, a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network is obtained.

[0045] In this embodiment, lithium triphosphate is used as the sintering aid, the mass ratio of carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes and lithium triphosphate is 6:3:1, zirconium oxide balls are used as the milling medium for high-energy ball milling, the ball milling time is controlled at 4 to 6 hours, the ball milling speed is controlled at 200 to 400 r / min, and the high-energy ball milling process needs to be carried out in an argon protective atmosphere.

[0046] The three-dimensional conductive coating network in this step is prepared by high-energy ball milling.

[0047] Example 2

[0048] A method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste comprises the following steps:

[0049] (1) Crushing and granulating photovoltaic silicon crystal waste: The photovoltaic silicon crystal waste is sent to a sand mill for sand milling. To avoid the introduction of metal impurities, the sand milling medium size is selected from 10um to 2nm zirconium oxide sand, preferably 2nm zirconium oxide sand, the sand milling time is 0.5 to 3h, preferably 3h, the dispersion solvent is a water-based solvent or an organic solvent, and the dispersion solvent is specifically 95% industrial ethanol solvent. The sand milling detects the silicon powder particle size D 50 In the range of 200 to 800 nm, preferably 250 nm.

[0050] (2) Preparation of silicon dioxide material: Add an excess of 2 mol / L NaOH solution to the sand-ground nanoscale photovoltaic silicon crystal slurry, stir it thoroughly for 2 hours to react and remove the metal element aluminum. Then filter and wash the product, and dry the silicon powder in a vacuum drying oven at 80°C to remove the surface moisture of the silicon powder. The drying time is about 24 hours. The dried silicon powder is sent to a sublimation furnace and sintered for 10 hours at a heating rate of 2°C / min and a sintering temperature of 300°C. The silicon dioxide block material is obtained by natural cooling.

[0051] (3) Preparation of lithium-rich silicon dioxide particles:

[0052] a. Pulverize the blocky silicon oxide with a sand mill. The dispersing solvent in the sand milling process is 95% to 99% ethanol, preferably 99% ethanol. 99% ethanol has higher volatility and faster subsequent drying speed. The sand milling time is 0.5 to 3 hours, preferably 3 hours. The sand milling medium is zirconium oxide sand with a size distribution of 10um to 2nm, preferably 2nm zirconium oxide sand, which improves the solubility and drying speed of the subsequent process. The size of the silicon oxide after sand milling is D 50 The sand-milled silicon dioxide is dissolved in 99% ethanol and dried by spray drying. The sand-milled slurry is spray-dried to obtain silicon dioxide particles. The feed temperature of the spray drying is 40 to 100°C, preferably 60°C, the outlet air temperature is 80 to 200°C, the air flow rate is 0.5 to 3 m / s, and the droplet size is controlled at 10 to 200 um.

[0053] b. The obtained dry silicon oxide particles and lithium-rich compounds are subjected to high-temperature solid-phase alloy reaction under the protection of an inert gas environment, and lithium-rich silicon oxide particles are obtained through high-temperature solid-phase alloy reaction. The particle size of silicon oxide powder is 1 to 30 um, the mass ratio of silicon oxide to lithium-rich compound is 1 to 100:1, the high-temperature solid-phase reaction time is 1 to 36 hours, the heating rate is controlled to be 2 to 20°C / min, the temperature is naturally cooled, the sintering temperature is 200 to 1200°C, the inert gas introduced is argon or nitrogen, and the gas flow rate is 0.2 to 10 L / min.

[0054] In this embodiment, the pre-lithiation reagent is prepared by compounding lithium carbonate, lithium silicate, and lithium oxide in a mass ratio of 4:4:2. The mass ratio of the compounded pre-lithium compound to the silicon dioxide particles is 100:11. The high-temperature solid-phase reaction time is controlled at 36 hours, the heating rate is 2°C / min, the sintering temperature is 200°C, argon is introduced as a protective gas, the gas flow rate is controlled at 10L / min, and the reaction is naturally cooled after completion.

[0055] (4) Preparation of lithium-rich silicon oxide particles with a carbon-coated structure: Carbon is coated on the surface of lithium-rich silicon oxide by high-temperature chemical vapor deposition, wherein the particle size distribution of lithium-rich silicon oxide powder is 1-50 um, the mass ratio of carbon-containing organic matter to lithium-rich silicon oxide powder is 100-500:1, the high-temperature reaction time is 1-20 hours, the heating rate is controlled at 1-25°C / min, and the temperature is naturally cooled. The sintering temperature is 300-1000°C, the furnace speed is 1-10 r / min, and the inert gas introduced is argon and nitrogen, mixed with a small amount of hydrogen, the inert gas supply flow rate is controlled at 1-10 L / min, and the inert gas: hydrogen: supply flow rate ratio is 1-15:1.

[0056] The carbon source materials selected in this embodiment are organic substances that are easily decomposed by heat - glucose, starch and polyvinyl alcohol, which are obtained by compounding in a mass ratio of 2:2:6. The mass ratio of the compounded carbon source material to the lithium-rich silicon oxide particles is 500:1. The reaction time is controlled at 1h, the heating rate is 25℃ / min, the sintering temperature is 1000℃, and the furnace body needs to maintain a reasonable rotation speed to ensure uniform coating. The rotation speed is controlled at 2r / min. During the reaction, inert gas argon needs to be introduced as a protective gas, and a small amount of hydrogen is introduced at the same time to adjust the decomposition process of the carbon source, control the deposition rate and morphology of carbon, promote the cracking of the carbon source, and prevent excessive deposition. The mass ratio of the mixed argon and hydrogen is 15:1, and the gas flow rate of argon is controlled at 6L / min.

[0057] (5) Constructing a three-dimensional conductive network of carbon-coated lithium-rich silicon oxide particles: The carbon-coated lithium-rich silicon oxide particles, single-walled nanotubes, and lithium-containing sintering aids are mixed and ball-milled, and the single-walled carbon nanotubes are wrapped on the surface of the lithium-rich silicon oxide particles to form a three-dimensional network structure, thereby obtaining a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network. In this step, single-walled carbon nanotubes are selected as the main framework for constructing the conductive network, and lithium-containing phosphates are added as sintering aids to improve the conductivity of the material.

[0058] The mass ratio of carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes and lithium-containing sintering aids is 5-8:1-4:1, and the ball milling medium can be selected from zirconium oxide balls, aluminum oxide balls and silicon nitride balls, etc. The ball milling time is 1-8 hours, and the ball milling speed is 150-600r / min. High-energy ball milling needs to be carried out in an inert gas protection atmosphere, and the selected inert gas is nitrogen or argon. After the ball milling, a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network is obtained.

[0059] In this embodiment, lithium triphosphate is used as the sintering aid, the mass ratio of carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes and lithium triphosphate is 7:4:1, zirconium oxide balls are used as the milling medium for high-energy ball milling, the ball milling time is controlled at 4 to 6 hours, the ball milling speed is controlled at 200 to 400 r / min, and the high-energy ball milling process needs to be carried out in an argon protective atmosphere.

[0060] The three-dimensional conductive coating network in this step is prepared by high-energy ball milling.

[0061] Example 3

[0062] A method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste comprises the following steps:

[0063] (1) Crushing and granulating photovoltaic silicon crystal waste: The photovoltaic silicon crystal waste is sent to a sand mill for sand milling. To avoid the introduction of metal impurities, the sand milling medium size is selected from 10um to 2nm zirconium oxide sand, preferably 2nm zirconium oxide sand, the sand milling time is 0.5 to 3h, preferably 3h, the dispersion solvent is a water-based solvent or an organic solvent, and the dispersion solvent is specifically 95% industrial ethanol solvent. The sand milling detects the silicon powder particle size D 50 In the range of 200 to 800 nm, preferably 250 nm.

[0064] (2) Preparation of silicon dioxide material: Add an excess of 0.1 mol / L NaOH solution to the sand-ground nanoscale photovoltaic silicon crystal slurry, stir it thoroughly for 2 hours to react and remove the metal element aluminum. Then filter and wash the product, and dry the silicon powder in a vacuum drying oven at 80°C to remove the surface moisture of the silicon powder. The drying time is about 24 hours. The dried silicon powder is sent to a sublimation furnace, sintered for 1 hour, with a heating rate of 8°C / min and a sintering temperature of 1100°C. The silicon dioxide block material is obtained by natural cooling.

[0065] (3) Preparation of lithium-rich silicon dioxide particles:

[0066] a. Pulverize the blocky silicon oxide with a sand mill. The dispersing solvent in the sand milling process is 95% to 99% ethanol, preferably 99% ethanol. 99% ethanol has higher volatility and faster subsequent drying speed. The sand milling time is 0.5 to 3 hours, preferably 3 hours. The sand milling medium is zirconium oxide sand with a size distribution of 10um to 2nm, preferably 2nm zirconium oxide sand, which improves the solubility and drying speed of the subsequent process. The size of the silicon oxide after sand milling is D 50 The sand-milled silicon dioxide is dissolved in 99% ethanol and dried by spray drying. The sand-milled slurry is spray-dried to obtain silicon dioxide particles. The feed temperature of the spray drying is 40 to 100°C, preferably 60°C, the outlet air temperature is 80 to 200°C, the air flow rate is 0.5 to 3 m / s, and the droplet size is controlled at 10 to 200 um.

[0067] b. The obtained dry silicon oxide particles and lithium-rich compounds are subjected to high-temperature solid-phase alloy reaction under the protection of an inert gas environment, and lithium-rich silicon oxide particles are obtained through high-temperature solid-phase alloy reaction. The particle size of silicon oxide powder is 1 to 30 um, the mass ratio of silicon oxide to lithium-rich compound is 1 to 100:1, the high-temperature solid-phase reaction time is 1 to 36 hours, the heating rate is controlled to be 2 to 20°C / min, the temperature is naturally cooled, the sintering temperature is 200 to 1200°C, the inert gas introduced is argon or nitrogen, and the gas flow rate is 0.2 to 10 L / min.

[0068] In this embodiment, the pre-lithiation reagent is prepared by compounding lithium carbonate, lithium silicate, and lithium oxide in a mass ratio of 4:4:2. The mass ratio of the compounded pre-lithium compound to the silicon dioxide particles is 30:66. The high-temperature solid-phase reaction time is controlled at 1 h, the heating rate is 20°C / min, the sintering temperature is 1200°C, argon is introduced as a protective gas, the gas flow rate is controlled at 0.2 L / min, and the reaction is naturally cooled after completion.

[0069] (4) Preparation of lithium-rich silicon oxide particles with a carbon-coated structure: Carbon is coated on the surface of lithium-rich silicon oxide by high-temperature chemical vapor deposition, wherein the particle size distribution of lithium-rich silicon oxide powder is 1-50 um, the mass ratio of carbon-containing organic matter to lithium-rich silicon oxide powder is 100-500:1, the high-temperature reaction time is 1-20 hours, the heating rate is controlled at 1-25°C / min, and the temperature is naturally cooled. The sintering temperature is 300-1000°C, the furnace speed is 1-10 r / min, and the inert gas introduced is argon and nitrogen, mixed with a small amount of hydrogen, the inert gas supply flow rate is controlled at 1-10 L / min, and the inert gas: hydrogen: supply flow rate ratio is 1-15:1.

[0070] The carbon source materials selected in this embodiment are organic substances that are easily decomposed by heat - glucose, starch and polyvinyl alcohol, which are obtained by compounding in a mass ratio of 2:2:6. The mass ratio of the compounded carbon source material to the lithium-rich silicon oxide particles is 300:1. The reaction time is controlled at 20h, the heating rate is 1°C / min, the sintering temperature is 300°C, and the furnace body needs to maintain a reasonable rotation speed to ensure uniform coating. The rotation speed is controlled at 2r / min. During the reaction, inert gas argon needs to be introduced as a protective gas, and a small amount of hydrogen is introduced at the same time to adjust the decomposition process of the carbon source, control the deposition rate and morphology of carbon, promote the cracking of the carbon source, and prevent excessive deposition. The mass ratio of the mixed argon and hydrogen is 1:1, and the gas flow rate of argon is controlled at 6L / min.

[0071] (5) Constructing a three-dimensional conductive network of carbon-coated lithium-rich silicon oxide particles: The carbon-coated lithium-rich silicon oxide particles, single-walled nanotubes, and lithium-containing sintering aids are mixed and ball-milled, and the single-walled carbon nanotubes are wrapped on the surface of the lithium-rich silicon oxide particles to form a three-dimensional network structure, thereby obtaining a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network. In this step, single-walled carbon nanotubes are selected as the main framework for constructing the conductive network, and lithium-containing phosphates are added as sintering aids to improve the conductivity of the material.

[0072] The mass ratio of carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes and lithium-containing sintering aids is 5-8:1-4:1, and the ball milling medium can be selected from zirconium oxide balls, aluminum oxide balls and silicon nitride balls, etc. The ball milling time is 1-8 hours, and the ball milling speed is 150-600r / min. High-energy ball milling needs to be carried out in an inert gas protection atmosphere, and the selected inert gas is nitrogen or argon. After the ball milling, a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network is obtained.

[0073] In this embodiment, lithium triphosphate is used as the sintering aid, the mass ratio of carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes and lithium triphosphate is 5:1:1, zirconium oxide balls are used as the milling medium for high-energy ball milling, the ball milling time is controlled at 4 to 6 hours, the ball milling speed is controlled at 200 to 400 r / min, and the high-energy ball milling process needs to be carried out in an argon protective atmosphere.

[0074] The three-dimensional conductive coating network in this step is prepared by high-energy ball milling.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that no silicon oxide sample is used, and silicon powder is directly used for subsequent operations. The specific properties are shown in Table 1.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that no pre-lithiation process is performed.

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 1 is that no carbon coating process is performed.

[0081] Comparative Example 4

[0082] The difference between this comparative example and Example 1 is that the subsequent three-dimensional conductive network structure construction process is not performed.

[0083] The present invention also provides a method for preparing an electrode sheet using the negative electrode material prepared above as follows:

[0084] a. Prepare a slurry with the prepared carbon-coated lithium-rich silicon oxide particles with a three-dimensional conductive network, acetylene black, and sodium carboxymethyl cellulose in a mass ratio of 6:2:2, and use deionized water and anhydrous ethanol as the solvent in a volume ratio of 7.5:2.5. Stir for 6 to 10 hours to prepare a uniform slurry;

[0085] b. The slurry is evenly coated on the Cu foil, the coating speed ratio is controlled at 20% to 30%, the temperature during the coating process is controlled at 85°C, and the slurry is placed in a vacuum drying oven for drying at a constant temperature of 90°C for 10 hours;

[0086] c. The processed electrode sheet is then compacted with a roller press and then punched into an electrode sheet with a diameter of 10 mm with a slicer, and a complete and crease-free electrode sheet is screened.

[0087] When the above-mentioned negative electrode sheet is subsequently used to prepare a button battery, the lithium sheet is used as the negative electrode, and the electrolyte is a 1M LiPF6 solution dissolved in a solvent of EC:DMC:DEC=4:4:2. After the electrode sheet and the positive electrode sheet, electrolyte, gasket and positive and negative electrode shells are assembled and buttoned, a sealing machine is used for sealing. Combined with the rolling process, the density of the electrode material can be increased and the capacity can be increased. Good contact is conducive to improving the efficiency of ion transfer.

[0088] To further verify the electrochemical performance of the material, the performance of the prepared carbon-coated lithium-rich silicon oxide material with a three-dimensional conductive network is tested in combination with the following examples. The protection scope of the present invention is not limited by the following examples.

[0089] The negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-4 were used as negative electrodes, and NCM811 ternary materials were used as positive electrodes to assemble batteries, and the batteries were subjected to electrochemical tests. The performance test method is as follows:

[0090] (1) First efficiency test: voltage range 0.001 ~ 3V. Charge and discharge current: 0.1C, discharge first then charge. First coulomb efficiency calculation method: first charge capacity / first discharge capacity.

[0091] (2) Rate performance test method: charge and discharge at rates of 0.1C, 0.2C, 0.4C, 0.8C, and 1.6C, with a voltage range of 0.001 to 3V, for 10 cycles each time, and charge and discharge at a rate of 0.1C for 200 cycles.

[0092] (3) Cyclic performance test method: charge and discharge at a rate of 0.5C and 1C, with a voltage range of 0.001 to 3V, and cycle 500 times.

[0093] (4) Impedance: Test standard: DCR (direct current resistance) is obtained by testing at room temperature (25°C), battery capacity state 50%, 2C, and discharge for 20s.

[0094] The battery performance test results are shown in Table 1.

[0095] Table 1 Battery performance test data

[0096]

[0097] The theoretical capacity of silicon oxide (2680mAhg -1 ) compared to pure silicon (3579mAhg -1), it can be seen from Example 1 and Comparative Example 1 that when carbon is coated on pure silicon, pyrolytic carbon undergoes a catalytic reaction, which makes it difficult to coat amorphous carbon on pure silicon. The battery prepared from this negative electrode material has poor cycle stability and low life, while silicon oxide has a better balance between capacity and cycle performance. It can be seen from Example 1 and Comparative Example 2 that pre-lithiated silicon oxide can improve the first coulombic efficiency of the material. It can be seen from Example 1 and Comparative Example 3 that the carbon coating layer will improve the conductivity of the material, and the outermost phosphorus-doped single-walled carbon nanotubes effectively suppress the volume expansion problem of silicon oxide materials during the lithium insertion process through their own excellent mechanical properties, reduce the breakage and reconstruction problems of the SEI film, and improve the stability of the material. At the same time, phosphorus doping can provide more electron donors, change the band gap width of the material, introduce band gap defect energy levels, and improve the conductivity of the material. This scheme first prepares silicon powder into silicon oxide powder, and then prepares a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network through a series of dry operations such as high-temperature pre-lithiation, high-temperature carbon coating, and high-energy ball milling. The dry process can reduce the amount of solvent used, thereby reducing the cost of reagents. In addition, reducing the use of chemical reagents also reduces the pollution of the production process to the environment. Finally, this application reduces the residual alkali content in the material during the preparation process, and the dry process weakens the influence of the solvent on the performance of the negative electrode material (such as capacity and cycle stability).

[0098] In addition to the above-mentioned pre-lithiation reagents, technicians in this field can also use one or more combinations of lithium-rich compounds such as lithium hydroxide, lithium carbonate, lithium silicate, lithium fluoride, lithium hydroxide, lithium sulfate, etc. as pre-lithiation reagents based on their own resource characteristics.

[0099] In addition to the above-mentioned carbon source materials, technicians in this field can also use one or more combinations of carbon-containing organic substances such as glucose, sucrose, polyols (glycerol), polyvinyl alcohol, polystyrene, starch, polyacrylonitrile, etc. as carbon source materials for carbon coating based on their own resource characteristics.

[0100] In addition to the above-mentioned lithium-containing sintering aids, technicians in this field can also use one or more substances selected from lithium oxyborate, lithium carbonate, lithium fluoride, lithium oxide, lithium chloride, lithium silicate, etc. in combination with lithium triphosphate as lithium-containing sintering aids based on their own resource characteristics.

[0101] Other similar reagents, and the selection of similar reaction parameters, those skilled in the art can determine the above-mentioned only embodiments of the present invention according to common knowledge, and the common knowledge such as the known specific structure, characteristics and reactant ratio in the scheme is not described too much here. It should be pointed out that for those skilled in the art, without departing from the concept of the present invention, several deformations and improvements can also be made, such as simply adjusting the selection of parameters within or near the specified parameter range, which should also be regarded as the protection scope of the present invention, which will not affect the effect of the implementation of the present invention and the practicality of the patent. The protection scope required by this application shall be based on the content of its claims, and the specific implementation methods in the specification and other records can be used to explain the content of the claims.

Claims

1. A method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste, characterized in that: The following steps are involved: Step 1: Crushing and granulating photovoltaic silicon crystal waste: crushing bulk photovoltaic silicon crystal waste to reduce its size to nanometer level; Step 2: Preparation of silicon dioxide material: dissolving the crushed photovoltaic silicon crystal waste in an organic solvent of NaOH, then filtering, washing and drying the product, and sending the dried silicon crystal waste into a sublimation furnace for sintering at a sintering temperature of 300 to 1100° C. to obtain a block of silicon dioxide material; Step 3: Preparation of lithium-rich silicon oxide particles: crushing and pulverizing the block silicon oxide material into nano-sized particles, and roasting the silicon oxide particles and the lithium-rich compound at a roasting temperature of 200 to 1200° C. to obtain lithium-rich silicon oxide particles; Step 4: Preparation of carbon-coated lithium-rich silicon oxide particles: reacting the lithium-rich silicon oxide particles with a carbon source compound at a temperature of 300 to 1000° C. to obtain lithium-rich silicon oxide particles with a sandwich structure, wherein the inner layer is silicon oxide, the middle layer is lithium-rich silicon oxide, and the outer layer is an amorphous carbon coating layer; Step 5: Construct a conductive network of carbon-coated lithium-rich silicon oxide particles: Mix and ball-mill the carbon-coated lithium-rich silicon oxide particles, single-walled nanotubes, and phosphorus-containing sintering aids. The single-walled carbon nanotubes are wrapped around the surface of the lithium-rich silicon oxide particles to form a three-dimensional network structure, thereby obtaining a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network.

2. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 1, characterized in that: In the step 1, the size of the photovoltaic silicon crystal waste is reduced by sand grinding.

3. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 2, characterized in that: In the sand-milling process of step 1, the dispersing solvent is a water-based solvent or an organic solvent, the sand-milling medium is zirconium oxide sand with a size of 10 um to 2 nm, and the sand-milling time is 0.5 to 3 hours.

4. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 1, characterized in that: In the step 2, the sintering oxidation time is 1 to 10 hours, the heating rate of the sintering temperature is 2 to 15° C. / min, and the temperature is naturally cooled after sintering; the concentration of the NaOH is 0.1 to 2 mol / L.

5. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 1, characterized in that: In step 3, the blocky silicon oxide is crushed into silicon oxide powder by sand milling. The dispersing solvent in the sand milling process is 95% to 99% ethanol. The sand milling time is 0.5 to 3 hours. The sand milling medium size is 10um to 2nm zirconium oxide sand. The size of the silicon oxide after sand milling is 10 to 900nm.

6. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 5, characterized in that: The sand-milled slurry in step 3 is spray-dried to obtain silicon oxide particles. The spray-drying feed temperature is 40-100° C., the outlet air temperature is 80-200° C., the air flow rate is 0.5-3 m / s, and the droplet size is 10-200 um.

7. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 6, characterized in that: The silicon oxide particles in step 3 are subjected to a high-temperature solid-phase alloy reaction with a lithium-rich compound under the protection of an inert gas condition to obtain lithium-rich silicon oxide particles; the lithium-rich compound comprises one or more of lithium hydroxide, lithium carbonate, lithium silicate, lithium fluoride, lithium hydroxide, and lithium sulfate; the particle size distribution of the silicon oxide powder is 1 to 30 um, the mass ratio of silicon oxide to lithium-rich compound is 1 to 100:1, the high-temperature solid-phase reaction time is 1 to 36 hours, the heating rate is controlled to be 2 to 20°C / min, and the reaction is cooled naturally; the inert gas is argon or nitrogen, and the gas flow rate is 0.2 to 10 L / min.

8. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 1, characterized in that: In the step 4, the amorphous carbon layer of the lithium-rich silicon oxide particles is formed by carbon coating generated by decomposition of carbon-containing organic matter at 300-1000°C. The lithium-rich silicon oxide particles react with the carbon-containing organic matter under inert conditions. The particle size distribution of the lithium-rich silicon oxide powder is 1-50um, the mass ratio of carbon-containing organic matter to lithium-rich silicon oxide powder is 100-500:1, the high-temperature reaction time is 1-20h, the heating rate is controlled to be 1-25°C / min, the furnace speed is 1-10r / min, the inert gas is argon or nitrogen mixed with hydrogen, the inert gas supply flow rate is controlled to be 1-10L / min, the inert gas supply flow rate ratio of inert gas to hydrogen is 1-15:1, and the reaction is naturally cooled after the reaction. The carbon-containing organic matter includes: one or more of glucose, sucrose, polyols, polyvinyl alcohol, polystyrene, starch, and polyacrylonitrile.

9. The method for preparing lithium-rich silicon oxide negative electrode material using photovoltaic crystalline silicon waste according to claim 1, characterized in that: In the step 5, a carbon-coated lithium-rich silicon oxide negative electrode material having a three-dimensional conductive network is prepared by high-energy ball milling under the protection of an inert gas; The lithium-containing sintering aid comprises: one or more of lithium oxyborate, lithium carbonate, lithium fluoride, lithium oxide, lithium triphosphate, lithium chloride, and lithium silicate; the mass ratio of carbon-coated lithium-rich silicon oxide particles, single-walled carbon nanotubes, and the lithium-containing sintering aid is 5-8:1-4:1, the ball milling medium is zirconia balls, alumina balls, or silicon nitride balls, the ball milling time is 1-8 hours, and the ball milling speed is 150-600 r / min.

10. A method for making an electrode sheet using the carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network according to any one of claims 1 to 9, comprising the following steps: a. Prepare a carbon-coated lithium-rich silicon oxide negative electrode material with a three-dimensional conductive network, acetylene black, and sodium carboxymethyl cellulose in a mass ratio of 6:2:2, then add deionized water and anhydrous ethanol, the volume ratio of deionized water to anhydrous ethanol is 7.5:2.5, stir for 6 to 10 hours, and prepare a uniform slurry; b. The slurry is evenly coated on the Cu foil, the coating speed ratio is controlled at 20% to 30%, the temperature during the coating process is controlled at 50 to 90°C, and after the coating is completed, the Cu foil is placed in a vacuum drying oven for drying at a constant temperature of 90°C for 10 hours to obtain a pole piece; c. Compact the electrode sheet with a roller press, and then punch it into an electrode sheet with a preset diameter with a slicer. Screen the electrode sheet to obtain a complete and crease-free electrode sheet. After assembling and buckling, use a sealing machine to seal it.

Citation Information

Patent Citations

  • Carbon-coated silicon-based negative electrode material and preparation method thereof

    CN112164779A

  • Three-dimensional coated silicon-based negative electrode material and preparation method thereof

    CN114464784A

  • Method for preparing silicon-carbon negative electrode by combining sanding with spray drying

    CN117199264A

  • Method for preparing carbon-coated porous silicon-based lithium battery negative electrode material from photovoltaic crystalline silicon waste

    CN118198324A

  • Lithium ion battery electrode material and preparation method therefor

    WO2021109965A1

Cited By

  • Silicon monoxide negative electrode material modified by utilizing photovoltaic waste back plate as well as preparation method and application of silicon monoxide negative electrode material

    CN121377050A

  • Method for preparing silicon-carbon material from photovoltaic waste silicon

    CN122380380A